Developing an education support system for disaster management through an ethnoscience-based digital disaster learning module - Bachri, Syamsul; Rahman Hakiki, A. Riyan; Wibowo, Novika Adi; Sumarmi; Amini, Risda; Yosritzal; Nursaribilah, Egi (International journal of disaster risk reduction, 2024)
Using evidence of the Mount Semeru eruption in 2021 shows the importance of community preparedness knowledge from an early age. This study aims to develop an ethnoscience-based digital module to improve the disaster preparedness of elementary school students around Mount Semeru. This is a development research using the stages of the ADDIE model. The procedure consists of five steps: Analysis, Design, Development, Implementation, and Evaluation (ADDIE). The stages start from needs analysis, designing instruments and module concepts, developing and testing the feasibility of module, implementing and testing the effectiveness of modules, and the last stage is module dissemination. The application of ethnoscience to digital modules through material on the history of Mount Semeru based on location, hazard, eruptions history, areas affected by eruptions, and eruption disaster preparedness. The research subjects consisted of 100 fifth-grade students and 10 teachers in three schools directly affected by the eruption of Mount Semeru with a pre-test and post-test one-group design. Data collection used interviews, questionnaires, and tests with quantitative descriptive analysis. The simple independent test is carried out by comparing the data before and after the implementation of the module. Module effectiveness test used an independent sample t-test with a value 0.000 < 0.05. The results showed that the ethnoscience-based digital module of volcanic eruption is very feasible and effective in improving the preparedness of elementary school students. In addition, as a finding of this study, the ethnoscience-based digital module promotes an education support system that is appropriate through the habits of local communities facing disasters contained in the module, which can provide a better understanding of students' perspectives related to the Semeru volcano disaster. The implication of the ethnoscience-based digital module for current knowledge is increasing the childhood awareness knowledge related to volcanic disaster based on local everyday life.